Evasão escolar e matemática no primeiro ano do ensino médio em uma escola da rede estadual em Castanhal/PA - ALENCAR, Sandro de Jesus da Silva (2022)
This study describes aspects that characterize school dropout related to the learning of Mathematics in a class of the 1st year of High School in a public state school of Castanhal - PA. Evasion is one of the great challenges that motivate debates and reflects in the scope of the Brazilian public education, because the permanence of the student in the school consists of a social problem with needs for investigations, as well as new proposals for public policies, once which encompasses several aspects and, when relating it to the discipline of Mathematics, it is possible to verify some relevant factors of this circumstance. The methodology employed consists of a qualitative descriptive approach, through which a questionnaire of open questions was applied to students and teachers, with the purpose of analyzing factors that contribute and challenge educators in their school routine. The results obtained indicate that external and internal factors can trigger the school dropout process. However, in the context of mathematics learning, different elements, such as learning difficulties, the absence of motivating methodologies and strict evaluation processes, have been affecting the dislike of the discipline and the failure of the evaluation grades and, consequently, in school dropout.